Their skeletons speak : Kennewick man and the Paleoamerican world - Walker, Sally M.; Owsley, Douglas W. (Minneapolis, MN : Carolrhoda Books, 2012)
Discusses the processes used by scientists to discern the identity of the Kennewick Man and what this nine thousand-year-old skeleton revealed about the arrival of humans in North America.
Prologue : Where to begin -- A day at the races -- The mystery deepens -- The stakes -- The Paleoamericans -- Kennewick Man's turn -- A body of evidence -- Grave matters -- Paleoamerican connections.
Includes bibliographical references (p. 130-132) and index.
Keywords: Kennewick Man; Human remains (Archaeology) -- Washington (State); Paleo-Indians -- Washington (State) -- Origin; Paleo-Indians -- Anthropometry -- Washington (State); Indians of North America -- Washington (State) -- Antiquities; Washington (State) -- Antiquities